Modeling steady state irrigated production: An empiracal application involving a two-crop rotation system and two state variables - Howitt, Rachel; MacEwan, Duncan; Msangi, Siwa (International Food Policy Research Institute, 2014)
In this paper we evaluate the intensive, extensive, and dynamic margin response to sustainable agricultural practices. We define sustainable agriculture as a system in which the resource and pollution stocks associated with production have a steady-state solution consistent with a resource-use path resulting in long run utility maximization. As an empirical application we consider two state variables, fertility levels and groundwater stocks, and a two-crop rotation system, alfalfa-cotton. Agricultural production leads to a fundamental tradeoff represented by the rotation between net-nitrogen using crops and net-nitrogen fixing crops. In addition, nitrogen using crops generally have higher net returns than nitrogen fixing crops, but nitrogen fixing crops have a higher water use per unit revenue. It follows that rotation shifts that favor nitrogen fixing crops result in greater groundwater depletion. To achieve sustainability in this context, one must simultaneously strike a steady-state balance, or at least a repeated cycle, between the rates of fertility change and changes in stocks of groundwater.